The occurrence of myxomycetes in wood. (October 2015) - Taylor, Katherine M.; Feest, Alan; Stephenson, Steven L.
Abstract: Although the fruiting bodies of myxomycetes are commonly found associated with coarse woody debris in forest ecosystems throughout the world, there is no direct evidence that these organisms actually live within wood. In the research reported herein, surface sterilisation of pieces of wood taken from the branches of eight different tree species and the subsequent culturing of slivers of wood collected from within the interior of those branches clearly revealed the presence of the amoeboflagellates of myxomycetes. No evidence of the occurrence of plasmodia within wood was found, but amoeboflagellates emerged from 47 % of the wood slivers placed in culture.